Implementasi Panel Surya Untuk Penerangan Green House milik Kelompok Wanita Tani Cempaka Kecamatan Lubuk Begalung - Alfitri, Nadia; Azra, Tuti; Andrizal, Andrizal; Yefriadi, Yefriadi; Mutaqin , Awaludin (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
Environmental parameters in a greenhouse influence plant growth, namely sunlight, air temperature, air humidity, which can be controlled more easily. Using a greenhouse allows you to get closer to optimal conditions for plant growth. A plant can generally grow in a warm and humid environment. Therefore, keeping plant seeds in a warm growing environment will speed up the plant growth process. Apart from the above parameters, it is also necessary to pay attention to disturbances from destructive animals at night which disturb fruit and vegetable crops. Since the existence of the green house, KWT has been active in helping the family's economy by planting vegetables such as soycin, celery, leeks, lettuce, eggplant and tomatoes. However, at night the Green House has no lighting. Because the green house is on empty land surrounded by weeds, there have been several incidents where animals have entered the green house and disturbed or damaged the plants, such as rats and raccoons. And it would be a shame if these plants were already bearing fruit like tomatoes and eggplant. Therefore, greenhouses need lighting in addition to maintaining temperature or warm conditions to speed up the seeding process and also to protect the plants in the greenhouse from nocturnal animals that damage fruit and vegetable plants. The team offers automatic lighting technology. also equipped with automatic watering.